Safety culture in construction industry / Edwin Tan Ai Yang - Edwin Tai , Ai Yang (2022)
The construction industry is top contributor of accidents in workplace in Malaysia. This industry had recorded 143 deaths and 8,191 accidents in 2018 alone. Therefore, change of safety culture in the industry is necessary for improved safety performance. Before any change can take place, assessing the existing safety culture is a must to determine the current situation. This study aimed to assess the safety culture of the local construction industry. A self-administered questionnaire was developed on Google Form and disseminated through SiswaMail and social medias. Targeted respondents are management-level construction personnel. The survey included demographic questions, safety-culture scale, and questions related to safety-culture factors. The safety-culture scale comprised 40 five-points Likert items under various dimensions and was analyzed by descriptive statistics to gauge the current level of safety culture of the industry. The mean value of the safety-culture assessment was “high” (N = 54, x̄ = 3.82) and more agreement than disagreement was generated indicating that respondents were satisfied with safety culture at their organizations. Besides that, relative importance index was performed to rank safety-culture factors by their perceived importance. The top 5 safety-culture factors are: 1) management commitment, 2) site management, 3) communication, 4) supportive environment, and 5) safety alignment. Furthermore, safety-culture assessment also identified two main areas for safety culture improvement: reporting culture and safety behaviour. Based on the literature and survey findings, a framework for improvement was developed to solve those issues.